Neurocomputational mechanisms underlying subjective valuation of effort costs - Chong, Trevor T.-J.; Apps, Matthew; Giehl, Kathrin; Sillence, Annie; Grima, Laura L.; Husain, Masud (PLOS Biology, 2017)
Model-based fMRI in humans shows that cognitive and physical motivation are underpinned by overlapping neural substrates, but the amygdala plays a unique role in valuation of cognitive effort.